Loewe, Tradition in Branding - Villanueva Fernández, María; Josa Martinez, Maria Eugenia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2016)
The constant renewal of image is part of the intrinsic essence of fashion itself. This rewenal is not possible without prior analysis of the past or, in other words, tradition. So, in many cases, tradition has become the key to the modernization of a brand´s identity and even the key to its success. In order to show how tradition influences the evolution of the brand image, the future communication aims to address the case study of Loewe as an example of this phenomenon. This research will address this issue through the study of the evolution of Loewe´s image, comparing the period of time from 1956 —when it started the renewal process of the firm towards modernity by Javier Carvajal and Vicente Vela among others—, until the present day —focused on the recovery of that brilliant age with Jonathan Anderson as creative director—